1994
DOI: 10.1182/blood.v84.8.2452.bloodjournal8482452
|View full text |Cite
|
Sign up to set email alerts
|

P2Z adenosine triphosphate receptor activity in cultured human monocyte- derived macrophages

Abstract: The present study shows that human mononuclear phagocytes express a P2Z- like purinergic membrane receptor activity. Extracellular adenosine triphosphate (ATP) induces the formation of nonselective membrane pores in human mononuclear phagocytes that allow the entry of otherwise membrane impermeant fluorescent dyes (YO-PRO-1 or Lucifer yellow) into the cytoplasm of these cells. The percentage of mononuclear phagocytes that was permeabilized by ATP increased as monocytes matured into macrophages. Their response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Like adenosine, these effects are mediated via specific cell membrane receptors. There are at least three different classes of ATP receptors, termed P2U/P2Y (G-protein-coupled, acting through release of Ca++ and phospholipase C), P2X (acting directly to activate ATP-ligand gated cation channels), and P2Z receptors, which mediate the opening of large "pores" in plasma membranes, making cells permeable to ions and molecules up to 900 daltons (90). The ATP receptors are encoded by a very large number of genes.…”
Section: Role Of Autotaxin In Tumour Motilitymentioning
confidence: 99%
“…Like adenosine, these effects are mediated via specific cell membrane receptors. There are at least three different classes of ATP receptors, termed P2U/P2Y (G-protein-coupled, acting through release of Ca++ and phospholipase C), P2X (acting directly to activate ATP-ligand gated cation channels), and P2Z receptors, which mediate the opening of large "pores" in plasma membranes, making cells permeable to ions and molecules up to 900 daltons (90). The ATP receptors are encoded by a very large number of genes.…”
Section: Role Of Autotaxin In Tumour Motilitymentioning
confidence: 99%
“…The phenomenon of ATP-induced cell membrane permeabilization has been shown, and partly characterized, in a variety of cell types [1,2,8,14,20]. Although it is generally accepted that the pore-forming P2z receptor, for which ATP 4serves as a ligand, plays a major role in the permeabilization t~,rocess, the mechanisms underlying this process are only i,artly understood [3,12,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The P2z is also a porefirming receptor in certain cells [4,[6][7][8] ,'/-methylene]triphosphate; TPP +, tetraphenylphosphonium; A0, the electrical potential across the cell membrane; 860, difference in A~ cell types, P2x in excitatory cells and P2z in certain cell types, like transformed and hemopoietic cells [8]. ATP-induced cell membrane permeabilization has been shown in many cells, including transformed mouse fibroblasts [2], mast cells [9], erythroleukemia cells [10], macrophages [11,12], Novikoff hepatoma cells [13], and certain other cells [8,14]. It is accepted by many investigators that permeabilization is mediated by the P2z receptor, but the mechanisms underlying this process are only partly understood [8].…”
Section: Introductionmentioning
confidence: 99%
“…Complementary DNA (cDNA) synthesis from the equivalent quantity of the total RNA was done using the Transcriptor First Strand synthesis kit (Roche). StepOnePlus™ Real-Time PCR system (Applied Biosystems) and SYBR green master mix (Ampliqon) were used to analyze the relative expression level of P2RX 1 , P2RX 2 , 14 and PANX1 genes. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene was used as the endogenous control.…”
Section: Analysis Of Gene Expression Using Real-time Quantitative Pmentioning
confidence: 99%
“…It affects intracellular calcium concentration in both human and murine macrophages. 13,14 It is demonstrated that alveolar macrophages have all subtypes of P2 receptors except P2Y 12 , P2X 2 , P2X 3 and P2X 6 .…”
mentioning
confidence: 99%